Metabolic changes that allow Plasmodium falciparum artemisinin-resistant parasites to tolerate oxidative stress - Bonive-Boscan, Alejandro David; Acosta, Héctor; Rojas, Ascanio (Frontiers in Parasitology, 2024)
Artemisinin-based treatments (ACTs) are the first therapy currently used to treat malaria produced by Plasmodium falciparum. However, in recent years increasing evidence shows that some strains of P. falciparum are less susceptible to ACT in the Southeast Asian region. A data reanalysis of several omics approaches currently available about parasites of P. falciparum that have some degree of resistance to ACT was carried out. The data used was from transcriptomics and metabolomics studies. One mitochondrial carrier of the parasite possibly involved in the mechanisms of tolerance to oxidative stress was modelled and subjected to molecular dockings with citrate and oxoglutarate. An increase in glutathione production was detected, changing the direction of the flux of metabolites in the tricarboxylic acid cycle, and boosting glucose consumed. The models of the mitochondrial carrier, called PfCOCP, show that it may be important in transporting citrate and oxoglutarate from the mitochondrial matrix to cytosol. If so, it may allow the parasite to tolerate the oxidative stress produced by artemisinin. This in-silico analysis shows that P. falciparum may tolerate the artemisinin's oxidative stress through metabolic changes not reported before, showing the need for further experimental research on the many metabolic aspects linked to this phenotype.